Hydrophilic polymer, method for manufacturing the same, and lithium secondary battery comprising a hydrophilic polymer
Patent Information
- Application Number
- KR1020237034979
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-06-15
- Publication Date
- 2026-09-04
- Estimated Expiration
- 2042-06-15
Smart Images

Figure 112023111877363-PCT00016_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to the field of lithium battery technology, and in particular to a hydrophilic polymer that can be used in a binder, a method for manufacturing the same, and a lithium-ion secondary battery comprising said hydrophilic polymer. Background Technology
[0002] With the rapid development of industries such as new energy vehicles, smartphones, and home appliances, market demand for lithium-ion batteries continues to increase, and the requirements for binders used in electrode manufacturing are also rising.
[0003] In conventional lithium-ion batteries, polyvinylidene fluoride (PVDF) has been widely used as a binder material due to its high dielectric constant and strong electrochemical corrosion resistance. However, polyvinylidene fluoride struggles to provide stable cycle performance due to its low adhesive strength and poor high-temperature electrochemical stability. Furthermore, when using polyvinylidene fluoride as a binder, organic dispersion media such as N-methylpyrrolidone (NMP) must generally be used as dispersants; however, these have disadvantages such as high flammability, explosiveness, volatility, toxicity, and high recovery costs. Therefore, the development of new water-based binders with excellent processability and adhesive performance is crucial.
[0004] As a result of diligent research to solve the above-mentioned problems, the inventors completed the present invention by copolymerizing a conjugated diene, a monoolefin, and a hydrophilic monomer having a structure represented by Formula I below, thereby discovering a binder with high adhesive strength and almost no floating or roll adhesion problems.
[0005] That is, the present invention relates to a hydrophilic polymer obtained by copolymerizing a conjugated diene, a monoolefin, and a hydrophilic monomer having a structure represented by the following formula I;
[0006] Formula I
[0007] In the formula, X1, X2, and X3 are each independently selected from hydrogen atoms or straight-chain or branched-chain alkyl groups having 1 to 4 carbon atoms; R1, R2, and R3 are each independent, at least one of which represents the same or different hydrophilic group, and the remainder represents a straight-chain or branched-chain alkyl group or alkoxy group selected from hydrogen atoms or having 1 to 4 carbon atoms. Accordingly, a copolymer modified with a hydrophilic monomer can be provided, said copolymer has improved hydrophilicity and adhesion, can improve affinity with materials such as graphite, and improves problems of floating and roll adhesion of the binder.
[0008] In a preferred embodiment of the hydrophilic polymer of the present invention, the hydrophilic polymer is a random copolymer; the conjugated diene is one or more of 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2,4-hexadiene, 1,3-cyclohexadiene, and 2-chloro-1,3-butadiene; and / or, the monoolefin is an aromatic monovinyl compound and may be selected from one or more of styrene, α-methylstyrene, p-tert-butylstyrene, butoxystyrene, vinyltoluene, chlorostyrene, and vinylnaphthalene. Accordingly, the hydrophilicity and adhesiveness of the hydrophilic polymer can be further improved.
[0009] In a preferred embodiment of the hydrophilic polymer of the present invention, the hydrophilic group is selected from at least one of a hydroxyl group, an amino group, and a carboxyl group, and may be selected as a hydroxyl group. Accordingly, the hydrophilicity and adhesiveness of the hydrophilic polymer can be further improved.
[0010] In a preferred embodiment of the hydrophilic polymer of the present invention, at least two of R1, R2, and R3 are hydrophilic groups, and the remainder are each independently selected from hydrogen atoms or alkyl groups having 1 to 4 carbon atoms. Accordingly, the hydrophilicity and adhesiveness of the hydrophilic polymer can be further improved.
[0011] In a preferred embodiment of the hydrophilic polymer of the present invention, X1 and X2 are hydrogen atoms, and X3 is selected from alkyl groups having 1 to 4 carbon atoms.
[0012] In a preferred embodiment of the hydrophilic polymer of the present invention, the number average molecular weight (Mn) is 12×10 4 ~17×10 4 am.
[0013] In a preferred embodiment of the hydrophilic polymer of the present invention, the mass ratio of the conjugated diene, monoolefin, and hydrophilic monomer in the hydrophilic polymer is 10 to 90:90 to 10:1 to 6. Accordingly, a hydrophilic polymer with stronger adhesive strength and non-gelling can be produced.
[0014] The present invention also relates to a method for producing a hydrophilic polymer comprising the step of polymerizing a conjugated diene, a monoolefin, and a hydrophilic monomer shown in Formula I to obtain the hydrophilic polymer;
[0015] Formula I
[0016] In the formula, X1, X2 and X3 are each independently selected from a hydrogen atom or a straight-chain or branched-chain alkyl group having 1 to 4 carbon atoms; R1, R2 and R3 have at least one hydrophilic group, and the remainder are each independently selected from a hydrogen atom or an alkyl group having 1 to 4 carbon atoms or an alkoxy group.
[0017] In a preferred embodiment of the method for preparing a hydrophilic polymer according to the present invention, the hydrophilic polymer is a random copolymer, and the conjugated diene is one or more of 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2,4-hexadiene, 1,3-cyclohexadiene, and 2-chloro-1,3-butadiene, and / or the monoolefin is selected from aromatic monovinyl compounds and may be one or more of styrene, α-methylstyrene, p-tert-butylstyrene, butoxystyrene, vinyltoluene, chlorostyrene, and vinylnaphthalene. Accordingly, the hydrophilicity and adhesiveness of the hydrophilic polymer can be further improved.
[0018] In a preferred embodiment of the hydrophilic polymer of the present invention, the hydrophilic group is selected from at least one of a hydroxyl group, an amino group, and a carboxyl group, and may be selected as a hydroxyl group. Accordingly, the hydrophilicity and adhesiveness of the hydrophilic polymer can be further improved.
[0019] In a preferred embodiment of the method for manufacturing a hydrophilic polymer of the present invention, at least two of R1, R2, and R3 are hydrophilic groups, and the remainder are each independently selected from hydrogen atoms or alkyl groups having 1 to 4 carbon atoms. Accordingly, the hydrophilicity and adhesiveness of the hydrophilic polymer can be further improved.
[0020] In a preferred embodiment of the hydrophilic polymer of the present invention, X1 and X2 are hydrogen atoms, and X3 is selected from alkyl groups having 1 to 4 carbon atoms.
[0021] In a preferred embodiment of the method for preparing a hydrophilic polymer of the present invention, the number average molecular weight (Mn) is 12×10 4 ~17×10 4 am.
[0022] In a preferred embodiment of the method for manufacturing a hydrophilic polymer according to the present invention, the mass ratio of the conjugated diene, monoolefin, and hydrophilic monomer in the hydrophilic polymer is 10 to 90:90 to 10:1 to 6. Accordingly, a hydrophilic polymer with stronger adhesive strength and that does not gel can be manufactured.
[0023] In addition, the present invention also relates to an electrode active material slurry comprising an electrode active material, a dispersion medium, and the hydrophilic polymer which is a binder. Optionally, the electrode active material slurry is a negative electrode active material slurry. Accordingly, an active material layer can be manufactured in which floating of the binder is suppressed and roll adhesion problems are reduced.
[0024] The present invention also relates to a lithium-ion secondary battery comprising a positive plate, a negative plate, a separator, and an electrolyte, wherein the negative plate comprises a negative film layer made of the electrode active material slurry. Accordingly, a lithium-ion secondary battery with a longer lifespan can be obtained.
[0025] The present invention also relates to a battery pack comprising the lithium-ion secondary battery. Accordingly, a battery pack with a longer lifespan can be obtained.
[0026] The present invention also relates to an electric device comprising at least one of the lithium-ion secondary battery and the battery pack. Accordingly, an electric device with a longer lifespan can be obtained. Brief explanation of the drawing
[0027] FIG. 1 is a schematic diagram of a secondary battery according to one embodiment of the present invention. FIG. 2 is an exploded view of a secondary battery according to one embodiment of the present invention shown in FIG. 1. FIG. 3 is a schematic diagram of a battery pack according to one embodiment of the present invention. FIG. 4 is an exploded view of a battery pack according to one embodiment of the present invention shown in FIG. 3. FIG. 5 is a schematic diagram of an electric device in which a secondary battery is used as a power source according to one embodiment of the present invention. Specific details for implementing the invention
[0028] The present invention will be described in detail below with appropriate reference to the attached drawings. However, unnecessary detailed descriptions may be omitted in some cases. For example, detailed descriptions of known matters and redundant descriptions of structures that are actually identical may be omitted. This is intended to prevent unnecessary duplication of the following description and to enable those skilled in the art to easily understand it. Furthermore, the attached drawings and the following description are provided to enable those skilled in the art to fully understand the present invention and are not intended to limit the subject matter described in the claims.
[0029] The “range” disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by the selection of one lower limit and one upper limit, and the selected lower limit and upper limit define the boundaries of a specific range. A range defined in this manner may or may not include endpoint values and may be arbitrarily combined. That is, any lower limit and any upper limit may be combined to form a single range. For example, if ranges of 60–120 and 80–110 are listed for a specific parameter, it should be understood that ranges of 60–110 and 80–120 are also considered. Furthermore, if minimum range values 1 and 2 are listed and maximum range values 3, 4, and 5 are listed, all ranges of 1–3, 1–4, 1–5, 2–3, 2–4, and 2–5 are expected. In the present invention, unless otherwise specified, a numeric range “a–b” represents an abbreviated expression of a combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range “0 to 5” means that all real numbers between “0 to 5” are listed in this specification, and “0 to 5” is merely an abbreviated expression for combinations of these numerical values. Additionally, if a specific parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is an integer, for example, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0030] Unless otherwise specified, all embodiments and optional embodiments of the present invention may be combined with one another to form a new technical solution.
[0031] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with one another to form a new technical solution.
[0032] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, and are preferably performed sequentially. For example, the method comprises steps (a) and (b), which indicates that the method may comprise steps (a) and (b) performed sequentially and steps (b) and (a) performed sequentially. For example, the mentioned method may further comprise step (c), which indicates that step (c) may be added to the method in any order, for example, the method may comprise steps (a), (b), and (c), steps (a), (c), and (b), steps (c), (a), and (b), etc.
[0033] Unless otherwise specified, "comprehensive" and "included" as used in the present invention may mean open and closed forms. For example, "comprehensive" and "included" may further encompass or include other unlisted components, or indicate that they encompass or include only the listed components.
[0034] Unless otherwise specified, the term "or" in the present invention is inclusive. For example, the phrase "A or B" indicates "A, B, or both A and B." More specifically, any one of the conditions satisfies both conditions "A or B": A is true (or exists) and B is false (or absent); A is false (or absent) and B is true (or exists); or A and B are both true (or exist).
[0035] In the present invention, unless specifically stated otherwise, "%" generally means "mass%" and "part" means "mass part".
[0036] As a water-based binder, the current mainstream solution is to use a styrene-butadiene copolymer (hereinafter also abbreviated as styrene-butadiene rubber or SBR) emulsion as a binder to form a slurry with carboxymethylcellulose (CMC), a thickening agent, and use it for bonding lithium battery negative electrode materials such as graphite.
[0037] In this slurry system, CMC is adsorbed onto the surface of hydrophobic graphite particles through a hydrophobic carboxyl group-unmodified main chain, and the graphite with adsorbed CMC is stably suspended in water through hydrophilic carboxyl groups. Adhesion of the lithium battery anode material is achieved by utilizing the good elasticity of SBR and the good dispersion effect of CMC.
[0038] However, due to the hydrophobicity of SBR, the compatibility of the graphite slurry is prone to deterioration after SBR and CMC are dispersed. In such aqueous CMC-SBR mixed binders, SBR is prone to floating during the slurry settling process in the cathode plate manufacturing process. Furthermore, due to the scattering of visible light by SBR particles, the scattering intensity of short-wavelength blue light is high, making slurry bluing prone to occur.
[0039] Furthermore, during the coating and drying process, uneven heating of the upper and lower parts of electrode plates, such as the cathode, and increased convection and capillary phenomena within the plates cause the SBR to easily rise to the surface of the plates due to moisture movement. Consequently, the dried binder is unevenly distributed along the longitudinal direction of the plates, leading to reduced adhesion between active materials and between the active materials and the current collector. This not only causes roll adhesion on the rolling surface of the cathode but, in severe cases, also results in film delamination, ultimately degrading battery performance.
[0040] The hydrophilic polymer of the present invention is obtained by free radical emulsion copolymerization of a conjugated diene, a monoolefin, and a hydrophilic monomer shown in Formula I below, and
[0041] Formula I
[0042] In the formula, X1, X2 and X3 are each independently selected from a hydrogen atom or a straight-chain or branched-chain alkyl group having 1 to 4 carbon atoms, R1, R2 and R3 have at least one hydrophilic group, and the remainder are each independently selected from a hydrogen atom or an alkyl group having 1 to 4 carbon atoms or an alkoxy group.
[0043] In the hydrophilic copolymer, the mass ratio of the conjugated diene, monoolefin, and hydrophilic monomer is 10 to 90:90 to 10:1 to 6, and more preferably 10 to 30:90 to 70:3 to 6.
[0044] Within a range that does not affect the effects of the present invention, conjugated dienes, monoolefins, and other monomers capable of copolymerizing with hydrophilic monomers may also be copolymerized.
[0045] Conjugated diene
[0046] Examples of conjugated dienes include conjugated dienes with 4 or more carbon atoms, such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2,4-hexadiene, 1,3-cyclohexadiene, and 2-chloro-1,3-butadiene. These conjugated dienes may be used individually or in combination of two or more types. From the perspective of increasing the peel strength of the electrode, 1,3-butadiene and isoprene are preferred. From the perspective of improving the thermal stability of the polymer and further enhancing the peel strength and moisture resistance of the electrode, 1,3-butadiene is more preferred.
[0047] In addition, to the extent that the purpose of the present invention is not impaired, the conjugated diene monomer may have substituents commonly used in the art, examples of such substituents include straight-chain or branched-chain C 1-6Examples include alkyl groups or their haloalkyl groups, and specific examples include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 2,2-dimethylpropyl, n-pentyl, 1-methylpentyl, 2-methylpentyl, 3-methylpentyl, 4-methylpentyl, 1,1-dimethylbutyl, 1,2-dimethylbutyl, 1,3-dimethylbutyl, 1,4-dimethylbutyl, 2,2-dimethylbutyl, 2,3-dimethylbutyl, 3,3-dimethylbutyl, and n-hexyl. In addition, examples of the above haloalkyl groups include the above straight-chain or branched-chain C 1-6 Examples include groups in which one or more hydrogen atoms of the alkyl group are substituted with fluorine, chlorine, bromine, or iodine.
[0048] monoolefin
[0049] Examples of monoolefins include compounds having one unsaturated ethylene bond, such as aromatic monovinyl compounds, or olefins such as ethylene and propylene; acrylic compounds such as (meth)acrylic acid, methyl (meth)acrylate, and butyl (meth)acrylate; halogenated olefins such as vinyl fluoride and vinyl chloride; unsaturated fatty acids such as oleic acid; and ethylene acetate and acrylonitrile. Aromatic monovinyl compounds are preferred.
[0050] Examples of aromatic monovinyl compounds include vinyl derivatives of monocyclic, polycyclic, or condensed-ring aromatic compounds, such as vinyl derivatives of benzene, biphenyl, naphthalene, anthracene, phenanthrene, perylene, and benzopyrene. Additionally, to the extent that the purpose of the present invention is not impaired, the vinyl derivatives of said aromatic compounds are C 1-6 Alkyl group, C 1-6They may have various substituents such as alkoxy groups and halogens. Examples of such monoolefins include styrene, α-methylstyrene, p-tert-butylstyrene, butoxystyrene, vinyltoluene, chlorostyrene, and vinylnaphthalene. Here, styrene is preferred in terms of improving the thermal stability of the particulate polymer and enhancing the peel strength and moisture resistance of the electrode. These monoolefins may be used individually or in combination of two or more types; it is preferable to use one individually.
[0051] hydrophilic monomer
[0052] The hydrophilic monomer of the present invention is a hydrophilic monomer shown in Formula I below, and
[0053] Formula I
[0054] In the formula, X1, X2 and X3 are each independently selected from a hydrogen atom or a straight-chain or branched-chain alkyl group having 1 to 4 carbon atoms; R1, R2 and R3 have at least one hydrophilic group, and the remainder are each independently selected from a hydrogen atom or an alkyl group having 1 to 4 carbon atoms or an alkoxy group.
[0055] In the above hydrophilic monomer, examples of the hydrophilic group include hydrophilic groups commonly used in the art that are easy to form hydrogen bonds, such as hydroxyl groups, amino groups, carboxyl groups, sulfonic acid groups, and phosphate groups. One or more of these hydrophilic groups may be present. In terms of improving the viscosity stability of the slurry composition and improving the peel strength of the electrode and resistance to harsh environments such as acids, bases, high temperatures, and high humidity, hydroxyl groups, amino groups, and carboxyl groups are preferred, hydroxyl groups and amino groups are more preferred, and hydroxyl groups are particularly preferred.
[0056] In the above hydrophilic monomer, there may be only one group selected from the hydrophilic groups, or there may be two or more. In terms of improving the viscosity stability of the slurry composition and improving the peel strength of the electrode and resistance to harsh environments such as acids, bases, high temperatures, and high humidity, it is preferable to have two hydrophilic groups, and it is more preferable that the two hydrophilic groups are located at the ortho position of the benzene ring.
[0057] In addition, when the total value of repeating units derived from monoolefins and conjugated dienes is 100 parts by mass, the amount of repeating units of hydrophilic monomers added is preferably 1 part by mass or more, more preferably 3 parts by mass or more, also preferably 6 parts by mass or less, and more preferably 4 parts by mass or less. If the amount of repeating units of hydrophilic monomers added is within the above range, the stability of the slurry composition can be improved, the coating density can be improved, and floating of the binder is suppressed, thereby suppressing roll adhesion problems during electrode plate rolling and further improving the electrode workability of the electrode composite material layer.
[0058] In the present invention, by copolymerizing a conjugated diene, a monoolefin, and a hydrophilic monomer to structurally improve the hydrophilicity of the binder, the binder has a stronger affinity with the active material, thereby fundamentally preventing floating during drying and roll adhesion problems during rolling.
[0059] Although the mechanism of improvement of the binder system by the hydrophilic polymer of such a structure is not yet clear, the inventors infer that this is due to covalent and non-covalent bonding actions caused by the hydrophilic group and aromatic ring in the hydrophilic polymer of the present invention. Specifically, since the hydrophilic polymer monomer of the present invention has an aromatic ring structure and at least one hydrophilic substituent, it has the following non-covalent bonding actions (i), (ii), (iii) and covalent bonding actions (iv).
[0060] (i) Hydrogen bonding action: In hydrophilic groups such as hydroxyl groups, amino groups, carboxyl groups, sulfonic acid groups, and phosphate groups, the non-hydrogen elements among them, such as O, N, P, and S, are very polar, so the hydrophilic group can easily form hydrogen bonds with other polar groups; and also, since the hydrophilic group has additional lone pairs of electrons, it can form hydrogen bonds with hydrogen atoms of other active groups.
[0061] (ii) Coordination: Since a non-hydrogen element is present in the hydrophilic group, the hydrophilic group has weak acidic / weak basic and strong reducing properties and strong metal coordination ability, Fe 3+ , Cu 2+ , V 3+ It readily forms chelates with metal ions and enables the curing of the binder by facilitating a phase transition from fluid to solid.
[0062] (iii) Stacking action: Since the hydrophilic polymer of the present invention has a benzene ring and is aromatic, its valence electrons participate in bonding as SP2 hybrid orbitals, easily interacting with other aromatic ring groups, e.g., aromatic ring groups in monoolefins, and SP2 hybrid electrons in active materials such as graphite. It implements electronic interactions by forming non-covalent bonds.
[0063] (iv) Covalent bonding action: In the hydrophilic groups of R1, R2, and R3, since the hydrophilic groups are all highly active, they are easily oxidized, which helps in the polymerization reaction. Additionally, they are easy to react with substances containing amino groups or mercapto groups, such as Schiff base reactions and Michael addition, to form stable covalent bonds and strengthen the adhesion of the binder.
[0064] The inventors infer that by using a copolymer of a hydrophilic monomer, a conjugated diene, and a monoolefin in the present invention, the affinity between the binder and the active material is structurally increased by utilizing the actions of (i), (ii), (iii), and (iv), thereby fundamentally preventing the problem of the binder floating during drying and the problem of roll adhesion during rolling.
[0065] Particularly preferably, when the hydrophilic groups of R1, R2, and R3 are two adjacent hydroxyl groups (-OH), that is, when the hydrophilic monomer forms a catechol structure, the polarity of the phenol hydroxyl groups is very strong, making it easy to form hydrogen bonds; it is strongly reducing yet weakly acidic and has a very strong metal coordination ability; and the valence electrons of the oxygen atom among them participate in bonding through SP2 hybrid orbitals to other aromatic ring groups Non-covalent bonds and electronic interactions can be easily implemented; the phenol hydroxyl group itself is very easily oxidized to produce highly chemically active phthaloquinone, which aids in polymerization reactions, and it is particularly desirable because it is easier to form stable covalent bonds to cure the binder, making it easier to cause reactions such as Schiff subtraction and Michael addition with substances containing amino or mercapto groups.
[0066] By copolymerizing a hydrophilic monomer, a conjugated diene, and a monoolefin during the synthesis process, the hydrophilicity of the copolymer itself is increased, and the adhesion between the active material and the current collector is improved, thereby improving the problem of electrode plate floating during the drying process.
[0067] Other monomers
[0068] The hydrophilic polymer of the present invention may include other monomers without affecting its properties. The other monomer is not particularly limited as long as it can copolymerize with the conjugated diene, monoolefin, and hydrophilic monomer. The other monomer can be polymerized together with the conjugated diene, monoolefin, and hydrophilic monomer to obtain a hydrophilic polymer; it is also possible to prepare a hydrophilic polymer by polymerizing the conjugated diene, monoolefin, and hydrophilic monomer, and then further copolymerize or graft polymerize the polymer.
[0069] Method for manufacturing a hydrophilic polymer
[0070] Another aspect of the present invention relates to a method for preparing a hydrophilic polymer, wherein the conjugated diene, monoolefin, and hydrophilic monomer are dispersed in a dispersion medium, and then, if necessary, an emulsifier and a molecular weight regulator are added to prepare a mixture, and then a copolymerization reaction is performed in the presence of an initiator to obtain a hydrophilic polymer or a dispersion thereof.
[0071] The polymerization method of conjugated dienes, monoolefins, and hydrophilic monomers is not particularly limited; however, in terms of active groups during polymerization, free radical polymerization, active free radical polymerization, cationic polymerization, or anionic polymerization may be cited; and in terms of the type of polymerization system, suspension polymerization, emulsion polymerization, or solution polymerization may be cited. In terms of ease of polymerization and post-treatment, free radical polymerization is preferred, and free radical emulsion polymerization is more preferred.
[0072] dispersion medium
[0073] The dispersion medium used in the present invention may be a dispersion medium generally used in copolymerization reactions, such as water, alcohol-based, ester-based, ether-based, ketone-based, alkane-based, halogenated alkane-based, amide-based, or a mixture thereof. From the perspective of environmental protection, water is preferred.
[0074] free radical initiator
[0075] The initiator used in the present invention may be a variety of water-soluble or oil-soluble free radical initiators generally used in free radical polymerization, and specific examples include azo compound systems such as azobis-isobutyronitrile, azobis-isoheptanonitrile, dimethylazobis-isobutylate initiator, and azobis-isobutylamidine hydrochloride; inorganic peroxide and persulfate systems such as hydrogen peroxide, ammonium persulfate, sodium persulfate, and potassium persulfate; and peroxide systems such as benzoyl peroxide, cumene peroxide, benzoyl tertiary butyl peroxide, and butyl ketone peroxide.
[0076] The amount of the above free radical initiator added is not particularly limited and can be added appropriately depending on the amount of the hydrophilic polymer, and when the total value of monomers constituting the structural unit of the hydrophilic polymer is 100 mass%, it is preferably 0.1 to 2%, more preferably 0.15 to 1%. By appropriately adjusting the amount of initiator used, the molecular weight of the hydrophilic polymer can be controlled.
[0077] In the hydrophilic polymer of the present invention, in order to realize improved viscosity stability of the slurry composition and peel strength of the electrode, and to consider ease of dispersion and coating of the slurry composition, the number average molecular weight of the hydrophilic polymer of the present invention is preferably 8×10 4 ~30X10 4 , more preferably 12X10 4 ~17X10 4 The molecular weight is the molecular weight converted to polystyrene by measuring it using gel permeation chromatography (GPC).
[0078] emulsifier
[0079] In the process of manufacturing the hydrophilic polymer of the present invention, an emulsifier or the like may be added as needed.
[0080] The emulsifier used in the present invention may be an emulsifier commonly used in free radical emulsion copolymerization, for example, anionic emulsifiers, cationic emulsifiers, nonionic emulsifiers, and amphoteric emulsifiers.
[0081] Examples of anionic emulsifiers include carboxylate (soap) type emulsifiers such as sodium oleate, potassium oleate, sodium stearate, potassium stearate, sodium rosinate, sodium laurate, potassium laurate, sodium naphthenate, and retinol soap; sulfonate type emulsifiers such as alkylbenzene sulfonate, α-olefin sulfonate, alkyl sulfonate, α-sulfomonocarboxylic acid ester, fatty acid sulfoalkyl ester, succinic acid sulfonate, alkylnaphthalene sulfonate, petroleum sulfonate, lignin sulfonate, and alkylglyceryl ether sulfonate; and sulfate ester type emulsifiers such as lauryl sulfate, alkyl sulfate, and allyl polyoxyethylene ether sulfate. Examples of phosphate-type emulsifiers include alkyl phosphate mono and diester salts, fatty alcohol polyoxyethylene ether phosphate mono and diester salts, and alkylphenol polyoxyethylene ether phosphate mono and diester salts.
[0082] Examples of cationic emulsifiers include alkylamine salts and quaternary ammonium salts such as lauryl ammonium chloride, cetyltrimethylammonium bromide, and cetylpyridinium bromide.
[0083] Examples of nonionic emulsifiers include nonionic emulsifiers or heterocyclic emulsifiers having ether groups, ester groups, and amide groups within the molecule, and specific examples include diol-type or polyol-type nonionic emulsifiers such as ethylene oxide, propylene oxide, ethylene oxide and propylene oxide block copolymer, and polyvinyl alcohol.
[0084] Examples of cationic emulsifiers include various amino acids and betaine-type cationic emulsifiers.
[0085] The amount of the above emulsifier added is not particularly limited and can be appropriately added depending on the amount of the hydrophilic polymer, and when the total value of the monomers constituting the structural unit of the hydrophilic polymer is 100 mass%, it is preferably 0.2 to 2%, more preferably 0.2 to 0.5%.
[0086] molecular weight regulator
[0087] In the process of manufacturing the hydrophilic polymer of the present invention, a molecular weight regulator, etc., may be added as needed.
[0088] In the hydrophilic polymer of the present invention, a molecular weight regulator may be added as needed to control the molecular weight of the copolymer. The molecular weight regulator used in the present invention may be an aliphatic mercaptan-based, xanthodic acid disulfide-based, polyphenol, etc., which are commonly used in free radical emulsion copolymerization, and specific examples include dodecyl mercaptan, dodecyl mercaptan acetate, dilauryl mercaptan oxalate, diisopropyl xanthate disulfide, phenol, eugenol, etc.
[0089] The amount of the molecular weight regulator added is not particularly limited and can be appropriately added according to the target molecular weight of the hydrophilic polymer. When the total value of monomers constituting the structural unit of the hydrophilic polymer is 100 mass%, the amount is preferably 0.1 to 1%, more preferably 0.1 to 0.5%. By appropriately adjusting the amount of the molecular weight regulator used, the molecular weight of the hydrophilic polymer can be controlled.
[0090] The emulsification method for copolymerizing the above-mentioned conjugated diene, monoolefin, and hydrophilic monomer is not particularly limited, and any emulsification method commonly used in the industry may be used. For example, various known emulsification dispersers may be used as emulsification equipment, and a specific example is IKA-LTRA-TURRAX. Furthermore, emulsification operation conditions using the emulsification disperser, such as processing temperature and processing time, are not particularly limited and can be selected according to the types of emulsifiers and free radical initiators, and should be appropriately selected to obtain the desired dispersion state.
[0091] In the above polymerization and emulsification, the types and amounts of additives such as emulsifiers, initiators, dispersion media, and molecular weight regulators have been exemplified; however, those skilled in the art should understand that the additives used above, such as emulsifiers, dispersion media, initiators, and molecular weight regulators, may be of generally used types and amounts, and should note that they may be appropriately adjusted depending on the polymerization method, etc.
[0092] In the present invention, the particle size of the hydrophilic polymer particles obtained after copolymerization is 80 to 400 nm, preferably 100 to 200 nm. As the particle size of the hydrophilic polymer particles decreases, the number of contact points between the binder and the active material increases, thereby increasing the adhesive strength. However, if the particle size is too small, it is easy to move during the drying process, which makes floating problems likely to occur. Secondly, if the particle size is too small, it affects the kinetic performance of the lithium-ion secondary battery. By ensuring that the hydrophilic polymer particles have the above particle size, good adhesive strength can be achieved while suppressing floating.
[0093] In addition, in this specification, the particle size of the hydrophilic polymer particles obtained after copolymerization refers to the particle size measured by laser diffraction.
[0094] In addition, to improve the viscosity stability of the slurry composition and the peel strength of the electrode, and to prevent slurry bluing and the resulting binder floating caused by insufficient polymerization, the copolymerization of the present invention is preferably stirred at a low temperature, under pressure, and at a low rotational speed. For example, hydrophilic polymer particles with a particle size within the above range can be obtained by copolymerizing at a temperature of 20 to 100°C, preferably 70 to 95°C, a pressure of 0.1 to 2.0 MPa, preferably 0.6 to 1.0 MPa, and a rotational speed of 100 to 250, preferably 150 to 200 rpm, which is particularly suitable for the manufacture of a slurry for manufacturing lithium-ion battery electrode plates.
[0095] In the dispersion obtained as described above, the solid content is 30 to 70%, preferably 40 to 60%. If the solid content is too low, the volume of the manufacturing equipment increases, and the manufacturing efficiency decreases; if the solid content is too high, there is a risk that the stirring will become uneven.
[0096] In addition, to improve the viscosity stability of the slurry composition and the peel strength of the electrode, and to prevent slurry bluing and subsequent binder floating caused by insufficient polymerization, it is preferable to control the pH value of the dispersion to 6 to 9 in the copolymerization of the present invention. The pH value can be controlled using an acid or base commonly used in the art, preferably a weakly acidic or weakly basic acid, such as acetic acid, hydrochloric acid, and sulfuric acid; or a base such as water ammonia, sodium hydroxide, potassium hydroxide, and diethylamino alcohol.
[0097] Active material slurry
[0098] The hydrophilic polymer of the present invention can be dispersed in a dispersion medium together with an electrode active material and other materials added as needed to prepare an active material slurry composition.
[0099] The electrode active material is not particularly limited, and various active materials included when forming the electrode plate described below can be used.
[0100] cathode plate
[0101] The cathode plate comprises a cathode current collector and a cathode film layer installed on at least one surface of the cathode current collector, and the cathode film layer comprises a cathode active material.
[0102] As an example, the cathode current collector has two opposing surfaces in the direction of its own thickness, and the cathode film layer is installed on either or both of the two opposing surfaces of the cathode current collector.
[0103] In some embodiments, the negative current collector may use a metal foil or a composite current collector. For example, the metal foil may be a copper foil. The composite current collector may include a polymer material substrate layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed on a polymer material substrate (e.g., polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.) by a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.).
[0104] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art. As an example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material, tin-based material, and lithium titanate. The silicon-based material may be selected from at least one of elemental silicon, silicon-oxygen compound, silicon-carbon complex, silicon-nitrogen complex, and silicon alloy. The tin-based material may be selected from at least one of elemental tin, tin oxide compound, and tin alloy. However, the present invention is not limited to these materials, and other general materials that can be used as battery negative electrode active materials may also be used. These negative electrode active materials may be used individually or in combination of two or more types.
[0105] In some embodiments, the cathode film layer further comprises a binder. The binder comprises a hydrophilic polymer of the present invention.
[0106] During the polymerization process, a hydrophilic monomer, a conjugated diene, and a monoolefin are copolymerized, thereby obtaining a hydrophilic polymer. When the above hydrophilic polymer is used as a binder, the hydrophilicity of the binder is significantly increased, which not only mitigates the phenomenon of the binder floating to the surface along with the evaporation of water during the drying process, but also, since the binder obtained in this way has structurally very strong adhesive properties, the adhesion strength between the active material and the electrode plate can be increased.
[0107] In some embodiments, the cathode film layer optionally further comprises a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0108] In some embodiments, the cathode film layer optionally further comprises other auxiliary agents such as a thickener (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0109] In some embodiments, the cathode plate may be manufactured by dispersing components for manufacturing the cathode plate, such as a cathode active material, a conductive agent, a binder, and any other components, in a solvent (e.g., deionized water) to form a cathode slurry; coating the cathode slurry onto a cathode current collector, and undergoing processes such as drying and cold pressing.
[0110] positive plate
[0111] The positive plate comprises a positive current collector and a positive film layer installed on at least one surface of the positive current collector, and the positive film layer comprises a positive active material.
[0112] As an example, the positive current collector has two opposing surfaces in the direction of its own thickness, and the positive film layer is installed on either or both of the two opposing surfaces of the positive current collector.
[0113] In some embodiments, the positive current collector may use a metal foil or a composite current collector. For example, the metal foil may be aluminum foil. The composite current collector may include a polymer material substrate layer and a metal layer formed on at least one surface of the polymer material substrate layer. The composite current collector may be formed on a polymer material substrate (e.g., a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.) by a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.).
[0114] In some embodiments, the positive electrode active material may be a positive electrode active material for a battery known in the art. As an example, the positive electrode active material may comprise at least one of a lithium-containing phosphate having an olivine structure, a lithium transition metal oxide, and a modified compound thereof. However, the present invention is not limited to these materials, and other general materials that can be used as positive electrode active materials for batteries may also be used. Such positive electrode active materials may be used alone or in combination of two or more. Here, examples of lithium transition metal oxides include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, and lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM 333 It may also be abbreviated as), LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM 523 It may also be abbreviated as), LiNi O. 5 Co 0.25 Mn 0.25 O2 (NCM 211 It may also be abbreviated as ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM 622 It may also be abbreviated as ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM 811 It may also be abbreviated as ), lithium nickel cobalt aluminum oxide (e.g., LiNi 0.85 Co 0.15 Al 0.05It includes, but is not limited to, at least one of O2) and modified compounds thereof. Examples of lithium-containing phosphates of an olivine structure include, but are not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (which may be abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron-manganese phosphate, and a composite material of lithium iron-manganese phosphate and carbon.
[0115] In some embodiments, the anode film layer further comprises a binder. The binder may comprise at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin, and may also comprise the hydrophilic polymer of the present invention.
[0116] In some embodiments, the anode film layer optionally further comprises a conductive agent. As an example, the conductive agent may comprise at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0117] In some embodiments, the positive plate may be manufactured by a method of forming a positive plate slurry by dispersing components for manufacturing the positive plate, such as a positive active material, a conductive agent, a binder, and any other components, in a solvent (e.g., N-methylpyrrolidone), coating the positive plate slurry onto a positive current collector, and then obtaining the positive plate through processes such as drying and cold pressing.
[0118] electrolytes
[0119] The electrolyte serves to transfer ions between the positive and negative plates. The present invention does not specifically limit the type of electrolyte and may select it as necessary. For example, the electrolyte may be a liquid, a gel, or both solid.
[0120] In some embodiments, the electrolyte is in a liquid state and includes an electrolyte salt and a solvent.
[0121] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonylimide, lithium bistrifluoromethanesulfonylimide, lithium trifluoromethanesulfonate, lithium dioxalate borate, lithium difluorophosphate, lithium difluorooxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0122] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0123] In some embodiments, the electrolyte optionally further comprises additives. For example, the additives may include a cathode film forming additive and an anode film forming additive, and may further include additives capable of improving specific performance of the battery, such as an additive for improving the overcharge performance of the battery and an additive for improving the high or low temperature performance of the battery.
[0124] Separator
[0125] In some embodiments, the secondary battery further comprises a separator. The present invention has no particular limitation on the type of separator, and a known porous separator with excellent chemical stability and mechanical stability may be selected.
[0126] In some embodiments, the material of the separator may be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multilayer composite film, but is not particularly limited thereto. If the separator is a multilayer composite film, the material of each layer may be the same or different, but is not particularly limited thereto.
[0127] In some embodiments, the positive plate, the negative plate, and the separator can be manufactured into an electrode assembly through a winding process or a lamination process.
[0128] In some embodiments, the secondary battery may include an external packaging. The external packaging is for packaging the electrode assembly and the electrolyte.
[0129] In some embodiments, the external packaging of the secondary battery may be a rigid case, such as a rigid plastic case, an aluminum case, a steel case, etc. The external packaging of the lithium-ion battery may be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of plastics include polypropylene, polybutylene terephthalate, polybutylene succinate, etc.
[0130] The present invention does not specifically limit the shape of the secondary battery, and it may be cylindrical, rectangular, or any other shape. For example, FIG. 1 illustrates an exemplary rectangular secondary battery (5).
[0131] In some embodiments, referring to FIG. 2, the outer packaging may include a case (51) and a cover plate (53). Here, the case (51) may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround to form a receiving cavity. The case (51) has an opening communicating with the receiving cavity, and the cover plate (53) may be installed over the opening to seal the receiving cavity. The positive plate, the negative plate, and the separator may be formed into an electrode assembly (52) through a winding process or a lamination process. The electrode assembly (52) is packaged within the receiving cavity. An electrolyte is infiltrated into the electrode assembly (52). The number of electrode assemblies (52) included in the secondary battery (5) may be one or more, which can be selected by a person skilled in the art according to specific needs.
[0132] In some embodiments, one or more secondary batteries (5) are assembled into battery modules (4) and then assembled into a battery pack (1). The number of battery modules (4) included in the battery pack (1) may be one or more, and the specific number may be selected by a person skilled in the art according to the application and capacity of the battery pack (1).
[0133] In addition, the present invention also provides an electric device. The electric device comprises one or more of a secondary battery, a battery module, or a battery pack provided in the present invention. The secondary battery, the battery module, or the battery pack may be used as a power source for the device or as an energy storage unit for the electric device. The electric device may be, but is not limited to, a mobile device (e.g., a mobile phone, a laptop computer, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0134] The above electrical device may select a secondary battery, a battery module, or a battery pack depending on the usage needs.
[0135] FIGS. 3 and 4 illustrate an exemplary battery pack (1). Referring to FIGS. 3 and 4, the battery pack (1) may include a battery box and a plurality of battery modules (4) installed in the battery box.
[0136] The battery box includes an upper box body (2) and a lower box body (3), and the upper box body (2) can be installed over the lower box body (3) and can form a sealed space for accommodating battery modules (4). A plurality of battery modules (4) can be arranged in the battery box according to any method.
[0137] FIG. 5 illustrates an exemplary electric device. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To satisfy the electric device's requirements for high power and high energy density of a secondary battery, a battery pack or a battery module may be used.
[0138] Other exemplary electrical devices may include mobile phones, tablet computers, laptop computers, etc. Since the devices generally need to be light and thin, they may use secondary batteries as a power source.
[0139] Examples
[0140] The present invention will be described in detail below based on examples, but those skilled in the art should understand that the following examples are merely illustrative and the present invention is not limited to these examples.
[0141] In addition, in the examples and comparative examples, the ratio of each monomer unit of the polymer of the present invention, solid content, average particle size, pH value, molecular weight, and roll adhesion degree, peel strength, and conductivity are measured and evaluated in the following ways.
[0142] Example 1
[0143] <Preparation of Hydrophilic Polymers>
[0144] 0.2 parts by mass sodium dodecylsulfonate as an emulsifier, 0.1 parts by mass potassium persulfate as an initiator, and 150 parts by mass distilled water as a dispersion medium were added to a 1000 ml pressurized reaction kettle and completely dissolved into a solution. Subsequently, 10 parts by mass 1,3-butadiene as a conjugated diene, 90 parts by mass styrene as a monoolefin, and 3 parts by mass 3,4-dihydroxystyrene as a hydrophilic monomer were added. The mixture was heated while stirring under conditions of 0.6 MPa, and when the temperature rose to 80°C, the reaction was maintained at this temperature for 6 hours to carry out the polymerization reaction. After the reaction was completed, the mixture was allowed to wait until the temperature dropped to 25°C, and then filtered to obtain an emulsion of the hydrophilic polymer. The emulsion solid content of the obtained hydrophilic polymer, the average particle size measured by a Malven particle size analyzer, the pH value measured by a PHS-3C precision pH meter, and the molecular weight (converted to polystyrene) measured by the GPC method are shown in Table 1. In addition, the results regarding the peel strength and roll adhesion of the electrode plate are also shown in Table 1.
[0145] Here, it should be noted that NMR measurements confirmed that the proportion derived from each monomer in the obtained hydrophilic polymer is approximately the same as the input ratio.
[0146] <Manufacturing of the Cathode Plate>
[0147] A cathode slurry composition having a solid content of 54% was obtained by sufficiently mixing 96.0 parts by mass of graphite as a cathode active material, 0.9 parts by mass of carbon black (SP) as a conductive agent, 1.5 parts by mass of carboxymethylcellulose (CMC) as a thickener, and 1.6 parts by mass of a hydrophilic polymer prepared as above with an appropriate amount of deionized water.
[0148] When preparing the slurry composition, a pure hydrophilic polymer extracted from a dispersion may be added, or a dispersion of a hydrophilic polymer may be added. When the hydrophilic polymer is added in the form of a dispersion, the amount added is the mass when converted to the pure hydrophilic polymer. Finally, the solid content in the cathode slurry composition was adjusted with an appropriate amount of deionized water. Considering ease of operation, preferably, after polymerizing the hydrophilic polymer, the hydrophilic polymer dispersion was used directly or filtered to prepare the cathode slurry composition.
[0149] Coating amount after drying is 282 mg / cm² 2 The above slurry was uniformly coated onto the surface of a copper foil, which is a cathode current collector, to reach [a certain level], and dried in an oven at 90°C to obtain a cathode raw material in which a cathode film plate was formed on the current collector.
[0150] Afterwards, the above-mentioned cathode material was rolled in an environment at a temperature of 25°C to obtain a cathode plate. The peel strength (peel force) of the cathode plate obtained in this way was measured in the following manner, and the degree of roll adhesion was evaluated. The results are shown in Table 1.
[0151] <Peel Strength Test>
[0152] In the peel strength test of the present invention, the cathode plate obtained after rolling was first cut into five uniform samples with a vertical length of 100.0 mm ± 0.1 mm and a horizontal width of 20.0 mm ± 0.1 mm. One surface to be tested was attached with double-sided tape, and the test surface was compressed with a 2 kg pressure roller to ensure that the double-sided tape and the cathode plate were completely bonded. The other surface of the double-sided tape was attached to the surface of a 304 stainless steel plate measuring 4 × 15 cm, and one end of the sample was bent in reverse. Then, one end of the stainless steel plate with the attached electrode plate was fixed to the upper clamp of an H-type tensioner, and the bent end of the sample was fixed to the lower clamp. The angle of the sample was adjusted so that the vertical axis of the peeled portion of the sample overlapped with the center connecting line of the upper and lower clamps, and the elasticity was made appropriate. Afterwards, under conditions of a temperature of 25±2℃ and relative humidity RH=65±5%, the sample was tensile at a speed of 50 mm / min until it was completely peeled off from the substrate, and the displacement and applied force were recorded during the process. The force at which the applied forces were balanced was defined as the peeling force of the electrode plate. The average value of the 5 results was defined as the peeling force.
[0153] <Evaluation of Roll Adhesion Degree>
[0154] Ten experts visually observed the degree of roll adhesion during the cathode plate manufacturing process, evaluated it using the following three-stage classification method, and used the average value of the evaluation as the evaluation value of the degree of roll adhesion.
[0155] ○: Roll adhesion is not observed or is barely observed
[0156] △: Slight roll adhesion, but peels off easily
[0157] ×: Cannot be peeled off due to severe roll adhesion
[0158] <Manufacturing of the Anode Plate>
[0159] 95 parts by mass of lithium iron phosphate as the positive electrode active material, 2.5 parts by mass of commercially available carbon black as a conductive agent, and 2.5 parts by mass of commercially available polyvinylidene fluoride as a binder were added and mixed in a planetary stirrer. Then, N-methylpyrrolidone, an organic solvent, was added and stirred and mixed at a temperature of 25±0.5℃ to obtain a positive electrode slurry composition having a viscosity of 11,000 mPa·s (measured at a temperature of 25±0.5℃ using a DV-2TLV Brookfield viscometer, rotor: 64#, rotor rotation speed: 12 rpm).
[0160] Coating amount after drying is 326±50 mg / cm² 2 The anode slurry composition obtained to reach [the desired result] was coated onto a current collector, which is an aluminum foil with a thickness of 13 μm. It was dried in an oven at 125°C to obtain an anode raw material in which an anode material layer was formed on the current collector.
[0161] After that, the above anode raw material was rolled in an environment at a temperature of 25℃ to obtain an anode plate.
[0162] <Manufacturing of Separator Membranes>
[0163] A general-purpose polyethylene porous membrane was prepared as a separator.
[0164] <Manufacturing of Lithium-ion Batteries>
[0165] A cell was obtained by stacking the above-mentioned negative electrode plate, positive electrode plate, and separator. The cell was assembled into an external package, filled with an electrolyte, and then packaged to obtain a lithium-ion battery. The battery performance was measured in the following manner, and the results are shown in Table 1.
[0166] < Method for testing the cycle performance of a secondary battery and measuring battery performance at room temperature >
[0167] In a 25°C environment, the lithium-ion secondary batteries prepared in each example and comparative example were charged and discharged once. After charging to 3.65V with a constant current and constant voltage of 1C, the batteries were left standing for 5 minutes at a cutoff current of 0.05C. Subsequently, a constant current discharge was performed at a discharge current of 1C to a lower charge cutoff voltage of 2.5V to record the first cycle discharge capacity. According to the above method, 500 charge and discharge cycles were performed on the batteries to record the 500 cycle discharge capacity. The cycle capacity retention rate of the secondary batteries was calculated as follows.
[0168] Cycle capacity retention rate (%) = (500 cycle discharge capacity / 1 cycle discharge capacity) × 100%.
[0169] Examples 2~46
[0170] Except for changing the ratio of polymerization monomers as shown in Table 1, all procedures were performed in the same manner as in Example 1 to prepare a hydrophilic polymer, a slurry composition for a negative electrode, a negative electrode plate, a positive electrode plate, a separator, and a lithium-ion battery. They were also evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0171] Comparative Example 1
[0172] A cathode slurry composition having a solid content of 54% was obtained by thoroughly mixing 96.0 parts by mass of graphite as a cathode active material, 0.9 parts by mass of carbon black (SP) as a conductive agent, 1.5 parts by mass of carboxymethylcellulose (CMC) as a thickener, and 1.6 parts by mass of general SBR with an appropriate amount of deionized water. Subsequently, a cathode plate, an anode plate, a separator, and a lithium-ion battery were manufactured in the same steps as in Example 1. They were also evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0173] Comparative Example 2:
[0174] Except for replacing the thickener of Comparative Example 1 with sodium carboxymethylcellulose and preparing a thickener by mixing highly substitutive guar gum with a degree of substitution of 1.6 in a mass ratio of 1:3, a cathode slurry composition, a cathode plate, an anode plate, a separator, and a lithium-ion battery were prepared in the same steps as Comparative Example 1. In addition, they were evaluated in the same manner as Example 1. The results are shown in Table 1.
[0175] Comparative Example 3:
[0176] A cathode slurry composition, a cathode plate, an anode plate, a separator, and a lithium-ion battery were prepared in the same steps as in Comparative Example 1, except that 1.6 parts by mass of a binder containing silicon dioxide coated with polymethacrylate was used instead of using the hydrophilic polymer of the present invention or a conventional SBR. In addition, they were evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0177] [Table 1]
[0178]
[0179]
[0180]
[0181]
[0182]
[0183] According to the results of Table 1 above, it can be seen that when a negative electrode binder and a negative electrode slurry are prepared using the hydrophilic polymer of the present invention, a lithium-ion battery with equivalent or better performance than before can be obtained by suppressing floating of the binder system and roll adhesion problems during negative electrode plate rolling, and improving the bonding strength between the active material and the current collector.
[0184] It should be noted that the present invention is not limited to the above embodiments. Within the scope of the technical solution means of the present invention, all embodiments having the same configuration as the technical concept and exhibiting the same operation and effect are included within the technical scope of the present invention. Furthermore, various modifications conceived by a person skilled in the art without departing from the concept of the present invention may be applied to the embodiments, and other forms configured by combining some components of the embodiments are also included within the scope of the present invention. Explanation of the symbols
[0185] 1: Battery pack; 2: Upper box body; 3: Lower box body; 4: Battery module; 5: Secondary battery; 51: Case; 52: Electrode assembly; 53: Cover plate.
Claims
Claim 1 As a hydrophilic polymer, this is a copolymer of a conjugated diene, a monoolefin, and a hydrophilic monomer represented by Formula I, and A hydrophilic polymer characterized in that, in Formula I, X1 and X2 are hydrogen atoms, X3 is selected from an alkyl group having 1 to 4 carbon atoms, R1, R2 and R3 each have at least one hydrophilic group, and the remainder are each independently selected from a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group, and the particle size of the hydrophilic polymer particles is 80 to 400 nm. Claim 2 A hydrophilic polymer according to claim 1, wherein the copolymer is a random copolymer, and the conjugated diene is a conjugated diene having 4 or more carbon atoms, selected from one or more of 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2,4-hexadiene, 1,3-cyclohexadiene, and 2-chloro-1,3-butadiene, and / or the monoolefin is an aromatic monovinyl compound, selected from one or more of styrene, α-methylstyrene, p-tert-butylstyrene, butoxystyrene, vinyltoluene, chlorostyrene, and vinylnaphthalene. Claim 3 A hydrophilic polymer according to claim 2, characterized in that the conjugated diene is selected as 1,3-butadiene, and / or the monoolefin is selected as styrene. Claim 4 A hydrophilic polymer according to claim 1, characterized in that the hydrophilic group is selected from at least one of a hydroxyl group, an amino group, and a carboxyl group. Claim 5 A hydrophilic polymer according to claim 4, characterized in that the hydrophilic group is selected as a hydroxyl group. Claim 6 A hydrophilic polymer according to claim 1, characterized in that at least two of R1, R2, and R3 are hydrophilic groups, and the remainder are each independently selected from hydrogen atoms or alkyl groups having 1 to 4 carbon atoms. Claim 7 In claim 1, the number average molecular weight (Mn) is 12×10 4 ~17×10 4 A hydrophilic polymer characterized by being. Claim 8 A hydrophilic polymer according to claim 1, characterized in that the mass ratio of the conjugated diene, the monoolefin, and the hydrophilic monomer in the hydrophilic polymer is 10 to 90:90 to 10:1 to 6. Claim 9 A method for preparing a hydrophilic polymer comprises the step of polymerizing a conjugated diene, a monoolefin, and a hydrophilic monomer represented by Formula I, and A method for preparing a hydrophilic polymer, characterized in that, in Formula I, X1 and X2 are hydrogen atoms, X3 is selected from an alkyl group having 1 to 4 carbon atoms, R1, R2 and R3 each have at least one hydrophilic group, and the remainder are each independently selected from a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group, and the particle size of the hydrophilic polymer particles is 80 to 400 nm. Claim 10 A method for preparing a hydrophilic polymer according to claim 9, wherein the hydrophilic polymer is a random copolymer, and the conjugated diene is a conjugated diene having 4 or more carbon atoms, selected from one or more of 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2,4-hexadiene, 1,3-cyclohexadiene, and 2-chloro-1,3-butadiene, and / or, the monoolefin is an aromatic monovinyl compound, selected from one or more of styrene, α-methylstyrene, p-tert-butylstyrene, butoxystyrene, vinyltoluene, chlorostyrene, and vinylnaphthalene. Claim 11 A method for producing a hydrophilic polymer according to claim 10, wherein the conjugated diene is selected as 1,3-butadiene and / or the monoolefin is selected as styrene. Claim 12 A method for manufacturing a hydrophilic polymer according to claim 9, characterized in that the hydrophilic group is selected from at least one of a hydroxyl group, an amino group, and a carboxyl group. Claim 13 A method for manufacturing a hydrophilic polymer according to claim 12, characterized in that the hydrophilic group is selected as a hydroxyl group. Claim 14 A method for preparing a hydrophilic polymer according to claim 9, characterized in that at least two of R1, R2, and R3 are hydrophilic groups, and the remainder are each independently selected from hydrogen atoms or alkyl groups having 1 to 4 carbon atoms. Claim 15 In claim 9, the number average molecular weight (Mn) is 12×10 4 ~17×10 4 A method for manufacturing a hydrophilic polymer characterized by the following. Claim 16 A method for preparing a hydrophilic polymer according to claim 9, characterized in that, in the hydrophilic polymer, the mass ratio of the conjugated diene, the monoolefin, and the hydrophilic monomer is 10 to 90:90 to 10:1 to 6. Claim 17 An electrode active material slurry comprising an electrode active material, a dispersion medium, and a hydrophilic polymer according to any one of claims 1 to 8 or a hydrophilic polymer prepared by a manufacturing method according to any one of claims 9 to 16, wherein optionally, the electrode active material slurry is a negative electrode active material slurry. Claim 18 A lithium-ion secondary battery comprising a positive electrode plate, a negative electrode plate, a separator, and an electrolyte, wherein the negative electrode plate comprises a negative electrode film layer prepared from an electrode active material slurry according to claim 17. Claim 19 A battery pack characterized by including a lithium-ion secondary battery according to claim 18. Claim 20 An electric device characterized by comprising a lithium-ion secondary battery according to claim 18. Claim 21 delete Claim 22 delete
Citation Information
Patent Citations
Copolymer, rubber composition, and tire
CN113174010A
Binder composition for electricity storage devices, slurry for electricity storage device electrodes, electricity storage device electrode, and electricity storage device
WO2020226035A1
Copolymer, rubber composition, and tire
JP2021116360A
Binder composition for non-aqueous secondary battery electrode, slurry composition for non-aqueous secondary battery electrode, electrode for non-aqueous secondary battery, and non-aqueous secondary battery
WO2022114199A1